PENGARUH PAJAK, RETRIBUSI DAERAH, DAU, DAN DAK TERHADAP ALOKASI ANGGARAN BELANJA MODAL - Wahyudi, Maria Valencia; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out whether Local Tax, Local Retribution, General Allocation Fund, and Special Allocation Fund, have influence to the Allocation of Capital Expenditure Budget on East Java districts/cities. The population and samples of this research are 6 Local Governments on district and cities in East Java. This research applies quantitative method which focuses on hypothesis test, analyzed the data, measured, and the conclusion is obtained is the generalization. The data collection method applies the purposive sampling method from the secondary data which has been done by collecting, recording, and processing the data which is related to the research during the last 5 years, in 2009-2013 periods. The data analysis has been done by using multiple linear regressions with SPSS (Statistical Product and Service Solutions) as the application instrument. The result of this research has proved that simultaneously local tax, local retribution, general allocation fund, and special allocation fund, have significant influence to the allocation of Capital Expenditure Budget on districts/cities in East Java, it can be explained by the value of Adjusted R Square is 0.904 which shows that the independent variable can explain the dependent variable which is 90.4% whereas the remaining is 9.6% is influenced by other factors. Partially the local retribution variable has significant influence to the allocation of capital expenditure budget whereas the local tax, general allocation fund, and special allocation fund do not have any significant influence to the allocation of capital expenditure budget. Keywords: Local Tax, Local Retribution, General Allocation Fund, Special Allocation Fund, Capital Expenditure.